2023
DOI: 10.3389/fneur.2023.1146015
|View full text |Cite
|
Sign up to set email alerts
|

Imaging biomarkers in the idiopathic inflammatory myopathies

Abstract: Idiopathic inflammatory myopathies (IIMs) are a group of acquired muscle diseases with muscle inflammation, weakness, and other extra-muscular manifestations. IIMs can significantly impact the quality of life, and management of IIMs often requires a multi-disciplinary approach. Imaging biomarkers have become an integral part of the management of IIMs. Magnetic resonance imaging (MRI), muscle ultrasound, electrical impedance myography (EIM), and positron emission tomography (PET) are the most widely used imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 166 publications
0
6
0
1
Order By: Relevance
“…Previous studies have confirmed DWI and ADC efficacy as useful clinical tools to identify the pattern of intramuscular disorders based on changes of free water motion and increasing cellularity [ 14 , 16 , 26 32 ]. Meyer et al .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed DWI and ADC efficacy as useful clinical tools to identify the pattern of intramuscular disorders based on changes of free water motion and increasing cellularity [ 14 , 16 , 26 32 ]. Meyer et al .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, muscle MRI has emerged as an important tool in the diagnosis of muscle disorders due to its ability to highlight affected muscle by revealing atrophy, fat infiltration and signs of inflammation [ 32 ]. In sIBM, MRI changes have been reported in both upper and lower limbs, are more severe in distal segments, and usually have an asymmetric pattern [ 32 , 33 , 34 , 35 ]. Fat infiltration is commonly seen in MRI scans [ 33 , 35 , 36 , 37 ].…”
Section: Diagnosis Of Sibmmentioning
confidence: 99%
“…sIBM is a male-predominant disease that has a prevalence of 5–71 per million in the whole population ( Tsamis et al, 2022 ). Typically occurring after the age of 50 ( Snedden et al, 2022 ), sIBM is characterized by progressive and asymmetric weakness in the quadriceps and long finger flexors rather than an acute or subacute symmetrical proximal muscle weakness seen in other subtypes of IIM ( Zubair et al, 2023 ). Individuals with sIBM experience a loss of muscle strength at a rate of 3.5%–28% per year ( Zubair et al, 2023 ) and can become wheelchair-bound at a median time of 10.5 years after the disease onset ( Skolka and Naddaf, 2023 ).…”
Section: Symptoms Diagnosis and Current Treatment Of Sibmmentioning
confidence: 99%
“…Typically occurring after the age of 50 ( Snedden et al, 2022 ), sIBM is characterized by progressive and asymmetric weakness in the quadriceps and long finger flexors rather than an acute or subacute symmetrical proximal muscle weakness seen in other subtypes of IIM ( Zubair et al, 2023 ). Individuals with sIBM experience a loss of muscle strength at a rate of 3.5%–28% per year ( Zubair et al, 2023 ) and can become wheelchair-bound at a median time of 10.5 years after the disease onset ( Skolka and Naddaf, 2023 ). Respiratory compromise and dysphagia are common risk factors for premature death in sIBM patients, which may account for their slight but significantly shortened lifespan when compared to healthy subjects ( Shelly et al, 2021 ).…”
Section: Symptoms Diagnosis and Current Treatment Of Sibmmentioning
confidence: 99%